2023
DOI: 10.1021/acsami.2c20527
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Ternary Near-Infrared Organic Photodetectors for Biometric Monitoring

Abstract: Near-infrared (NIR) small-molecule acceptors that absorb at wavelengths of up to 1000 nm are attractive for applications in organic photodetectors (OPDs) and biometrics. In this study, we incorporated IEICO-4F as the third component for PffBT4T-2OD:PC 71 BM-based OPDs to provide an efficient NIR response while greatly suppressing the leakage current at reverse bias. By varying the blend ratio and thickness (250−600 nm), we obtained an NIR OPD displaying an ultralow dark-current density (J D = 2.62 nA cm −2 ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Through comparison, it is found that these BF X TQ-based optoelectronic devices can achieve both photodetection and emission in the NIR (II) region, which exhibits comparable or superior properties to previously reported organic semiconductor devices with single optoelectronic functionalities in terms of wavelength or performance. For the photodetectors, the detectivity at 1064 nm can reach 1.76 × 10 14 Jone, which is comparable to some NIR photodetector properties (Figure a). ,,, In addition, rod-shaped cocrystals can be fabricated as optical waveguide devices to realize a low optical-loss coefficient of 0.0097 dB/μm at 950 nm. This excellent optical performance is comparable to the previous studies in both the visible and NIR regions, showing superior photon transmission characteristics, which contributes to the highly promising applications in the field of photonics information technology (Figure b). ,, …”
Section: Resultsmentioning
confidence: 66%
“…Through comparison, it is found that these BF X TQ-based optoelectronic devices can achieve both photodetection and emission in the NIR (II) region, which exhibits comparable or superior properties to previously reported organic semiconductor devices with single optoelectronic functionalities in terms of wavelength or performance. For the photodetectors, the detectivity at 1064 nm can reach 1.76 × 10 14 Jone, which is comparable to some NIR photodetector properties (Figure a). ,,, In addition, rod-shaped cocrystals can be fabricated as optical waveguide devices to realize a low optical-loss coefficient of 0.0097 dB/μm at 950 nm. This excellent optical performance is comparable to the previous studies in both the visible and NIR regions, showing superior photon transmission characteristics, which contributes to the highly promising applications in the field of photonics information technology (Figure b). ,, …”
Section: Resultsmentioning
confidence: 66%
“…Under the assumption that shot noise predominantly governs the total noise, the D * could be simplified. This shot-noise-limited D * should be determined using the following equation: D * = R A B i normaln true≅ R A B i normals normalh normalo normalt true= R 2 q J normald …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the noise spectrum density ( S n ) of different devices was measured to calculate D * under −0.1 V bias by the low frequency noise test system. The specific detectivity was calculated using the following equation, 66–68 where A is the effective area of OPD, B is the normalized bandwidth (1 Hz), and S n is the noise spectrum density in A Hz −1/2 .…”
Section: Resultsmentioning
confidence: 99%